2012
DOI: 10.5603/cj.2012.0084
|View full text |Cite
|
Sign up to set email alerts
|

5-fluorouracil induced cardiotoxicity: Review of the literature

Abstract: 5-fluorouracil (5-FU) is a key chemotherapeutic agent in the treatment (Cardiol J 2012; 19, 5: 453-458)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(152 citation statements)
references
References 50 publications
3
143
0
6
Order By: Relevance
“…The functionality of the dual-organ platform was first validated using capecitabine, a prodrug that can undergo enzymatic activation by hepatocytes to the active form 5-fluorouracil (5-FU), which is a thymidylate synthase inhibitor thus inhibiting DNA synthesis (57). Once converted to 5-FU, it would exert increased cardiotoxicity compared to capecitabine (58). Indeed, we were able to reproduce such a process using our human heart-and-liver-on-chips platform (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…The functionality of the dual-organ platform was first validated using capecitabine, a prodrug that can undergo enzymatic activation by hepatocytes to the active form 5-fluorouracil (5-FU), which is a thymidylate synthase inhibitor thus inhibiting DNA synthesis (57). Once converted to 5-FU, it would exert increased cardiotoxicity compared to capecitabine (58). Indeed, we were able to reproduce such a process using our human heart-and-liver-on-chips platform (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…1,2 We show that prompt recognition of cardiogenic shock from fulminant myocarditis secondary to 5-FU cardiotoxicity-followed by the initiation of ECMO on an emergency basis-can provide adequate tissue perfusion and thereby an opportunity for myocardial recovery after discontinuation of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 The exact mechanism is currently unclear, but the authors of a systematic review 5 have proposed multifactorial underlying causes, including endothelium-dependent and -independent pathways, direct myocardial damage from cytotoxic effects, induction of apoptosis, rheological side effects, and the production, during drug storage, of cardiotoxic metabolite precursors (for example, fluoro acetate). [6][7][8][9][10][11][12] Animal models of 5-FU cardiotoxicity have manifested apoptosis of myocytes, endothelial cells, or both, which gives rise to clinical presentations similar to that of myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Th e therapy was discontinued and the patient was transferred to our intensive care unit because the electrocardiogram (ECG) showed ischemic changes. Th e fi rst ECG showed ST elevation and peaked T waves in D I-III , aVL, aVF and V [2][3][4][5][6] derivations as well as reciprocal changes in aVR and V I ( Figure 1). Detailed history revealed that a coronary angiography revealing non-pathological fi ndings was performed two weeks ago as a result of a similar clinical picture in another center.…”
Section: Case Presentationmentioning
confidence: 99%
“…It is frequently used in the treatment of gastrointestinal, breast, head and neck tumors and has cardiotoxic eff ects. Angina pectoris, acute myocardial infarction, supraventricular and ventricular tachycardia, coronary dissection, congestive heart failure, cardiomyopathy, myopericarditis, cardiogenic shock and sudden death are most serious cardiac side eff ects 1,2 . Th e frequency of cardiotoxicity is reported to be between 1.2-18% 3 .…”
Section: Introductionmentioning
confidence: 99%